Effect of dentine conditioning on adhesion of resin‐modified glass ionomer adhesives. (June 2014) - Hamama, HH; Burrow, MF; Yiu, C
Abstract Background The aim of this study was to investigate the use of phosphoric acid as a surface treatment compared to traditional conditioning agents to dentine bonded with resin‐modified glass ionomer (RMGIC) adhesives. Methods Forty human molars were utilized in microtensile bond strength testing, while another 16 were used for evaluation of the bonded interface with scanning electron microscopy. Three RMGIC adhesives were evaluated: Fuji Bond LC (GC Corp); Riva Bond LC (SDI Ltd); and Ketac N100 (3M‐ESPE). Surface treatments were 37% phosphoric acid (5 s) or 25–30% polyacrylic acid (PAA) (10 s), or the manufacturer's method – Fuji Bond LC: Cavity Conditioner (20% PAA + 3% AlCl3 10 s) or Ketac N100 primer: Ketac Nano priming agent (15 s). Teeth were finished with 600‐grit SiC paper, surfaces treated and bonded with RMGIC adhesive and stored in distilled water for 24 h then subjected to microtensile bond strength testing. Results Two‐way analysis of variance (ANOVA) revealed adhesion was affected by the 'type of RMGIC adhesive' and 'method of dentine surface treatment' (p < 0.05). The microtensile bond strength of Ketac N100 primer groups was lower than Fuji Bond LC and Riva Bond LC (p < 0.05). Conclusions For RMGIC adhesives a brief etch with phosphoric acid does not adversely effect short‐term bond strengths, but is no better than traditional conditioning with PAA.